Diets, Foods and Food Components Effect on Dyslipidemia - Fogacci, Federica; Cicero, Arrigo; Borghi, Claudio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Dyslipidemia, and particularly hypercholesterolemia, remains a main cardiovascular disease risk factor, partly reversible with the improvement of life-style, including dietary, habits. Even when a pharmacological treatment is begun, dietary support to lipid-lowering is always desired. This book will provide a selection of new evidence on the possible lipid-lowering effects of some dietary and medicinal plant components, reporting some interesting reviews, experimental data and results from clinical trials. The book is adapted for experts in nutrition but also for all scientists involved in cardiovascular disease prevention.